KAJIAN SISTEM PENGUKURAN KINERJA PABRIK GULA (STUDI KASUS : PG SUBANG JAWA BARAT) - Rohmatulloh Rohmatulloh; Marimin Marimin; Machfud Machfud; M. Zein Nasution (Jurnal Manajemen & Agribisnis, 2009)
The best apllying practice of performance management can lead to increase business competitiveness. The objective of this study was to describe of how performance measurement systems that has been conducted at PG Subang West Java to achive success areas of sugarcane factory. The systems was built to adopt from integrated dynamic performance systems (IDPMS) model. The models integrates of four functional areas : corporate management, plant management, shop floor, and process improvement teams (bina sarana tani and lab. QC). Each fungsional areas were linked through the specification, reporting, and dynamic updating of the defined areas of success, performance measure, and performance standard. Understanding  interrelationships of performance measurements provides the foundation for more focused improvement efforts